India and the Patent Wars Pharmaceuticals in the New Intellectual Property Regime - Halliburton, Murphy (ILR Press/Culture and Politics of Health Care Work, 2017)
India and the Patent Wars examines struggles over patents and access to medicine among pharmaceutical producers, activists and others under a new global intellectual property regime. In the past two decades, intellectual property rights have expanded throughout the globe creating a world in which protections for patents and copyrights have increased and a growing range of knowledge and practices are claimed as property. Driving these changes are U.S. court decisions, the policies of multinational corporations, and the World Trade Organization (WTO). Resistance to this regime has emerged in low-income countries among public health activists concerned about the rising cost of medicines for HIV/AIDS and indigenous peoples who now see their knowledge as vulnerable and pursue ownership claims for their medical and cultural practices.